Análise da influência das características do substrato e da ausência de ancoragem no reforço de vigas submetidas ao cisalhamento utilizando manta de fibra de carbono - Betencourt, Josiani Fatima (Universidade do Vale do Rio dos Sinos, 2025)
The present study investigates the use of carbon fiber sheets, without anchorage, for the shear strengthening of reinforced concrete beams, thereby assessing the impact caused by potential bonding failures of the sheet. Carbon fiber sheets exhibit characteristics such as high tensile strength, corrosion resistance, durability, and ease of installation, making them an excellent alternative for structural strengthening, especially in cases of architectural constraints. To develop this research, a literature review was conducted in order to deepen the understanding of fiber-reinforced polymers, their properties for use as structural reinforcement, as well as design and detailing techniques. The experimental phase consisted of the fabrication of four batches of reinforced concrete beams, with three beams in each batch, all with the same longitudinal and transverse reinforcement configuration. The first batch was used as a reference, while the others were strengthened: one batch was bonded by the Quartzolit team, and the remaining ones had intentional bonding defects introduced, in order to evaluate their performance in comparison with the others. The test carried out was a three-point bending test with an offset load, designed to induce shear failure. Deformation, displacements, and crack patterns were also analyzed in each tested element. The results showed that beams strengthened with intentional bonding defects achieved values up to 101.55% higher than the average of the reference beams, whereas other elements, despite showing increased strength, yielded lower results. Furthermore, changes in crack patterns and failure modes were observed when compared to the reference beams, where all failures occurred by diagonal tension. Based on the results obtained, the importance of proper preparation of the beam to be strengthened, as well as the use of anchorage devices, became evident, since some failures were caused by sheet debonding along the edges. Nevertheless, this study highlighted the efficiency of carbon fiber sheets as shear reinforcement, confirming their effectiveness among the materials available in civil engineering.
Keywords: Manta de fibra de carbono; Ancoragem; Reforço; Polímeros reforçados com fibra; Cisalhamento; Vigas; Concreto armado; Resistência; Carbon fiber sheet; Anchorage; Strengthening; Fiber-Reinforced Polymers; Shear; Beams; Reinforced concrete; Strength; ACCNPQ::Engenharias::Engenharia Civil